Autentisitas Influencer, Hubungan Parasosial, dan Kepercayaan Generasi Z terhadap Influencer TikTok - Raid Naufaijlal; Rendra Widyatama (Mediakom : Jurnal Ilmu Komunikasi, 2026)
This study examines influencer authenticity and parasocial relationship as predictors of trust in TikTok influencers among Generation Z users in the Special Region of Yogyakarta. Trust is treated as an audience judgment directed at the influencer as a communication source rather than merely as brand trust or purchase intention. A cross-sectional online survey involved 492 eligible respondents aged 18–26 years. To strengthen instrument validation, the sample was randomly divided into a calibration subsample (n = 246) and a validation subsample (n = 246). The questionnaire used a five-point Likert scale and 15 core indicators. In the calibration subsample, all retained items showed corrected item–total correlations above 0.40. In the validation subsample, a three-factor confirmatory model showed good fit (CFI = 0.977; TLI = 0.972; RMSEA = 0.037). Multiple regression with HC3 heteroskedasticity-consistent standard errors indicated that authenticity (β = 0.369; p < 0.001) and parasocial relationship (β = 0.441; p < 0.001) were positively associated with trust. The model explained 55.2% of the variance in trust. Commonality analysis showed unique contributions of 7.3% for authenticity and 10.4% for parasocial relationship, while 37.5% was explained jointly. A 5,000-resample bootstrap indicated that the difference between standardized coefficients was not statistically reliable. Trust in TikTok influencers is therefore better understood as being associated with intertwined evaluative and relational processes rather than with the dominance of a single predictor.